Kepemimpinan Kepala Sekolah dan Dampaknya Terhadap Pengelolaan Pada SMA Tegar Kelana Suranadi - Indiani Indiani, Indian Indiani; Setiadi, Dadi; Waluyo, Untung (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
One of the problems faced by school principals under the auspices of the foundation is that there is a dual leadership between the head of the foundation and the headmaster which causes administrative activities to be hampered so that the process of improving the quality of education in educational units led by the principal is hampered. The purpose of this study is to describe the principal's leadership style in carrying out his role as managerial. This research was conducted at Tegar Kelana West Lombok High School.This study uses a qualitative approach to the type of grounded theory. Data and data sources used are primary and secondary data with purposive sampling techniques, while for data collection using interviews, documentation and triangulation techniques. Data analysis uses the interactive model (interactive mode). This study describes the principal's leadership style and its impact on the management of Tegar Kelana High School principals, which refers to Permendiknas No. 19 of 2007 concerning Education Management Standards by the Primary and Secondary Education Unit and National Education Minister's Regulation no. 13 of 2007 and No. 28 of 2010 concerning Managerial Principals. The results of the study illustrate the leadership style of principals who tend to use selling styles and participating styles, which have an impact on less effective school management